2017
DOI: 10.1111/rego.12150
|View full text |Cite
|
Sign up to set email alerts
|

Interest group representation in the formal design of European Union agencies

Abstract: This article examines the decision to include interest group representation (IGR) in the most important decisionmaking bodies of European Union agencies (EAs). The study shows that there is considerable variation among agencies: some agencies have no IGR, others have formal rules that establish a clear distribution of the number of representatives among stakeholders, while other agencies are ambiguous with regard to the number of representatives that each group should have. In addition, interest group represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…For instance, in a recent study Busuioc and Jevnaker (2020) find that in the absence of legislator guidance, EU agencies have embraced very different engagement models for their stakeholder committees: some opting for narrow interest representation, while others having attempted to bypass 'thorny' issues of representation altogether by being 'open to all'. Such variation of stakeholder engagement across EU agencies is in line with other studies (Arras & Braun, 2018;Borrás et al, 2007;Perez Duran, 2018) and raises crucial questions as to their eventual effect. Either approach can come with potential pitfalls: Narrow structures can facilitate blind spots and biases and create possibilities for capture while broad churches' too, can raise the prospect of coalition-building outside legislator control (and its associated democratic costs) (Bertelli & Busuioc, 2020).…”
Section: Varieties Of Stakeholder Engagement In Regulatory Governancesupporting
confidence: 80%
“…For instance, in a recent study Busuioc and Jevnaker (2020) find that in the absence of legislator guidance, EU agencies have embraced very different engagement models for their stakeholder committees: some opting for narrow interest representation, while others having attempted to bypass 'thorny' issues of representation altogether by being 'open to all'. Such variation of stakeholder engagement across EU agencies is in line with other studies (Arras & Braun, 2018;Borrás et al, 2007;Perez Duran, 2018) and raises crucial questions as to their eventual effect. Either approach can come with potential pitfalls: Narrow structures can facilitate blind spots and biases and create possibilities for capture while broad churches' too, can raise the prospect of coalition-building outside legislator control (and its associated democratic costs) (Bertelli & Busuioc, 2020).…”
Section: Varieties Of Stakeholder Engagement In Regulatory Governancesupporting
confidence: 80%
“…To perform legislative oversight, legislators aim for a certain balance of interests by institutionalising the participation of organised interests representing interests other than regulated industries (McCubbins and Schwartz 1984;Kelemen 2002). For instance, previous research on EU agencies has indicated that most EU agency advisory committees are legally required by the founding regulation to involve stakeholders other than the regulated sector, and several EU agencies' legal statutes also contain requirements regarding such involvement (Arras and Braun 2018;Pérez Durán 2018). Agencies that have such legal requirements will invest more in contacts with nonregulated interests.…”
Section: Hypothesesmentioning
confidence: 99%
“…Much literature on the regulatory state directs attention specifically to the regulatory agencies that have been established to shape the behavior of market-based actors (e.g. Heims 2015;Heims 2017;Jordana et al 2018;Pérez Durán 2018). In this paper, we build on Levi-Faur's (2014, p. 600) argument that the boundaries of the regulatory state "are wider than are usually understood" and his advocacy that we explore "the ever-expanding and diversifying dimensions of the administrative state."…”
Section: Local Political Economy and The Regulatory State: Extensionsmentioning
confidence: 99%
“…Heims 2015; Heims 2017; Jordana et al . 2018; Pérez Durán 2018). In this paper, we build on Levi‐Faur's (2014, p. 600) argument that the boundaries of the regulatory state “are wider than are usually understood” and his advocacy that we explore “the ever‐expanding and diversifying dimensions of the administrative state.” In doing so, we hook into a body of “regulation for welfare” scholarship, now seeking to map the wide range of mechanisms through which contemporary public policy is operationalized (e.g.…”
Section: Local Political Economy and The Regulatory State: Extensionsmentioning
confidence: 99%